Impact of Acupuncture on Sleep and Comorbid Symptoms for Chronic Insomnia: A Randomized Clinical Trial - Wang C (Nature and Science of Sleep, 2021)
Cong Wang,1,* Wen-lin Xu,1,* Guan-wu Li,2 Cong Fu,1 Jin-jin Li,1 Jing Wang,1 Xin-yu Chen,3 Zhen Liu,1 Yun-fei Chen1 1Department of Acupuncture and Moxibustion, Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 2Department of Radiology, Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Traditional Chinese Medicine, Shanghai, People’s Republic of China; 3Acupuncture and Tuina Academy, Beijing University of Chinese Medicine Dongfang College, Hebei, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yun-fei Chen; Zhen LiuDepartment of Acupuncture and Moxibustion, Yueyang Hospital of Integrated Traditional Chinese and Western Medicine, Shanghai University of Traditional Chinese Medicine, No. 110 Ganhe Road, Hongkou District, Shanghai, 200437, People’s Republic of ChinaTel/Fax +86-21-65162628Email icyf1968@163.com; liuzhen8918@163.comStudy Objectives: To evaluate the efficacy and safety of acupuncture at HT 7 (Shenmen) and KI 7 (Fuliu) on sleep and comorbid symptoms for chronic insomnia.Methods and Design: A randomized, single-blind, parallel and sham-controlled trial consisted of an acupuncture group (n = 41) and a sham acupuncture group (n = 41). Setting: a tertiary hospital of integrated Chinese and Western medicine. Participants: 82 subjects with chronic insomnia based on the International Classification of Sleep Disorders, Third Edition (ICSD-3). Interventions: a 10-session acupuncture treatment at bilateral HT 7 and KI 7 or sham acupoints with shallow needling was performed over 3 weeks. Measurements: the Pittsburgh sleep quality index (PSQI) and insomnia severity index (ISI) were evaluated at baseline, posttreatment, and at two follow-ups as the primary outcome measures. Polysomnography (PSG) on two consecutive nights, the Beck anxiety inventory (BAI), the Beck depression inventory (BDI) fatigue severity scale (FSS) and the Epworth sleepiness scale (ESS) were evaluated at baseline and posttreatment as the secondary outcome measures.Results: After the treatments, PSQI scores decreased by 5.04 in the acupuncture group and 2.92 in the sham acupuncture group. ISI scores decreased by 7.65 in the acupuncture group and 5.05 in the sham acupuncture group. The between-group differences in the primary outcome measures posttreatment were statistically significant. However, no differences were found between the two groups during the two follow-ups. Regarding the PSG data, there were significantly lower levels of sleep onset latency (SOL), a lower percentage of sleep stage N1 and a higher percentage of sleep stage N3 in the acupuncture group than in the sham acupuncture group. After treatment, there were lower levels of comorbid symptoms (BAI, BDI, FSS and ESS) in both groups. However, no significant differences were observed between the groups.Conclusion: Acupuncture at HT 7 and KI 7 is an effective and safe nonpharmacologic intervention option for chronic insomnia.Clinical Trial Registration: The study was registered at the Chinese Clinical Trial Registry, registration ID: ChiCTR1900023787, China.Keywords: acupuncture, chronic insomnia, sleep and comorbid symptoms, randomized clinical trial